“Efecto de cuatro dosis de tetra hormona en la produccion de cultivo de tomate (lycopersicum esculentum Mill.) variedad rio grande en el distrito de Lamas” - Pérez Torres, Milagros (2014)
The present investigation entitled "Effect of four doses of tetrahormona crop production in tomato (Lycopersicon esculentum Mill) variety Ria Grande in the District of Lamas" aimed to assess and analyze the effect of four doses of tetrahormona (Biogyz) in the production of the tomato crop and perform economic analysis. Statistical design of randomized complete block (RCBD) was used, using five treatments and three replications. The results were: The T4 (0,6 l.ha-1 ) and T3 (0,5 l.ha-1 ) treatments were statistically equal and averaging Kg.ha 231,646.35 210,636.73 Kg.ha-1 reached the highest average yield per hectare, statistically outperforming all other treatments. The T4 (0,6 Lha-1 ) and T3 (0,5 l.ha-1 ) statistically equal and averaging 32,5 and 31, 1 fruit per plant reached statistically higher mean overcoming the other treatments. The T4 (0,6 l.ha-1 ) and T3 (0,5 l.héf1 ) and statistically equal averaging 120,8 g treatment and 115,2 g of fruit weight reached statistically higher mean beating the other treatments. The effect of increasing applications tetrahormona determined positive responses in progressive linear increase in performance Kg.ha-1 , number of flower clusters, fruit length, fruit weight, number of harvested fruits and plant height. The T4 (0,6 l.ha-1 ) treatment had the best cost / benefit ratio with 3.52, followed by T3 (0,5 l.ha-1 ) with 3,29, T2 (0,4 l. ha-1 ) with 2.48, T1 (0.3 l.ha-1 ) with 2.01 and TO (control) to 1,36 . Key words: Effect, tetrahormonal, Biogyz, variety, tomate, yield, production, dose.